AIAA Atmospheric Flight Mechanics Conference and Exhibit 2004
DOI: 10.2514/6.2004-5053
|View full text |Cite
|
Sign up to set email alerts
|

Transonic Free-To-Roll Analysis of the F/A-18E and F-35 Configurations

Abstract: The free-to-roll technique is used as a tool for predicting areas of uncommanded lateral motions. Recently, the NASA/Navy/Air Force Abrupt Wing Stall Program extended the use of this technique to the transonic speed regime. Using this technique, this paper evaluates various wing configurations on the pre-production F/A-18E aircraft and the Joint Strike

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The static and FTR testing were both done in the NASA Langley 12-Foot Low-Speed Tunnel. The experiments were conducted at sea-level pressure and density with a freestream dynamic pressure of 4 psf resulting in a mean aerodynamic chord-based Reynolds number of 0.5X10 6 . Although numerous configurations were tested, the paper will present LEX vents closed and LEX vents open with the LEF = 10', TEF = 30', and ailerons = 300 (symmetric trailing-edge-down deflection).…”
Section: Experimental Approachmentioning
confidence: 99%
“…The static and FTR testing were both done in the NASA Langley 12-Foot Low-Speed Tunnel. The experiments were conducted at sea-level pressure and density with a freestream dynamic pressure of 4 psf resulting in a mean aerodynamic chord-based Reynolds number of 0.5X10 6 . Although numerous configurations were tested, the paper will present LEX vents closed and LEX vents open with the LEF = 10', TEF = 30', and ailerons = 300 (symmetric trailing-edge-down deflection).…”
Section: Experimental Approachmentioning
confidence: 99%
“…28 The work was also conducted for the scaled-down F/A-18E to analyze the effect of configuration changes at transonic speeds. 29 Subsequently, wing-body rock for four military aircrafts, such as the F-16c and the F/A-18C were analyzed; 30,31 the results showed that the rolling motions had nonzero mean roll angles. In addition, the works of Williams et al also confirmed this property of x-31.…”
Section: Introductionmentioning
confidence: 99%
“…The classical FTR test technique offered promise for shedding additional light on the flight dynamics and aerodynamics of the lateral motions of the vents-open and vents-closed pre-production F/A-18E configurations. Owens et al 5 ' 6 reported on an extensive study of transonic uncommanded lateral motions of military aircraft using the free-to-roll technique, including the pre-production F/A-18E. The motivations, methods, and objectives for the application of the FTR method to the PA configuration parallel those for the transonic FTR tests of the pre-production F/A-1 8E.…”
Section: This Paper Is Declared a Work Of The Us Government And Is mentioning
confidence: 99%
“…In order to quantify the lateral activity a FOM was used similar to the one developed by Owens et al 5 ' 6 . The FOM is calculated from the roll-angle time histories and captures amplitude and rate effects.…”
Section: B Free To Roll Testingmentioning
confidence: 99%
See 1 more Smart Citation